Lipid Oxidation, Color Changes, and Microbiological Quality of Frozen Beef Burgers Incorporated with Shirazi Thyme, Cinnamon, and Rosemary Extracts - Hadi Hashemi Gahruie; Seyed Mohammad Hashem Hosseini; Mohammad Hossein Taghavifard; Mohammad Hadi Eskandari; Mohammad-Taghi Golmakani; Ehsan Shad (Journal of Food Quality)
In this study, the oxidative stability of beef burgers incorporated with Shirazi thyme, cinnamon, and rosemary extracts was compared with that of BHT-incorporated and antioxidant-free samples. The chemical composition, TBARS, metmyoglobin, pH, color, and microbial and sensory characteristics were evaluated during storage at −18°C for 2 months. The results indicated that Shirazi thyme and cinnamon extracts did not change the colorimetric properties significantly (P<0.05). Incorporating natural antioxidants led to a significant (P<0.05) reduction in TBARS (36.58–46.34%) and metmyoglobin (16.25–18.47%) as compared to control. Except for the control sample, total microbial counts of burgers were lower than the maximum allowed limit. Burgers formulated with Shirazi thyme revealed the lowest amount of total count. Regarding the sensory characteristics, the overall acceptability of different samples decreased in the order of cinnamon > BHT > Shirazi thyme > rosemary > control. Finally, the results showed that these plant extracts can be utilized as an alternative to synthetic antioxidants in formulation of burgers.